Experimental study on the pathogenesis of Salmonella give in dogs - Habasha, F. G.; S. Aziz ‎,; Yassin Ghani, Taha (The Iraqi Journal of Veterinary Medicine, 2009)
Experiment study was done on the pathogenicity of Salmonella give infections in dogs . Theexperiment was carried out on 8 puppies ranging in age from 8-9 weeks. The puppies were divided randomlyinto two equal groups. Group I inoculated orally with 4.8x109 Salmonella give and group II saved as control.The disease was characterized by acute gastroenteric and septicemic forms with variable severity. The mostconsistent clinical signs were anorexia, fever, diarrhea, vomiting repression and recumbancy. Salmonella wasconsistently isolated from blood as well as from feces. Gross pathological changes and histologicalexamination were characterized by sever congestion and inflammatory cells in the most of GIT